Psychoanalysis of the study of Law in the 21st century. Evolution, revolution or cachexia? - Barona Vilar, Silvia (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The University of the XXI Century is experiencing a moment of boiling and profound change. Social transformation is influencing the redefinition of the objectives of the University, its contents, its protagonists, its management and also the teaching and research methodology. What is taught, why, where, who teaches and to whom are some of the keys that offer answers to this metamorphosis of the Academy. Globalization, internationalization, digitalization, emigration and also the pandemic are factors that affect the metamorphosis of the University, in its goals and in its means, in people and in the material and structural instruments for its development.